2015
DOI: 10.1159/000369752
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling Pathway Reveals a Spatio-Temporal Correlation with the Size of Primordial Follicle Pool in Mice

Abstract: Background: The Hippo signaling pathway, a highly conserved cell signaling system, exists in most multicellular organisms and regulates cell proliferation, differentiation, and apoptosis. It has been reported that the members of Hippo signaling are expressed in mammalian ovaries, but the exact functions of this pathway in primordial follicle development remains unclear. Methods: To analyze the spatio-temporal correlation between the core component of Hippo pathway and the size of primordial follicle pool, West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Our recent results revealed that the Hippo signaling pathway is expressed in mouse ovaries and the expression of the core components of the Hippo pathway change during mouse follicular development [42]. In this study, as seen in Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our recent results revealed that the Hippo signaling pathway is expressed in mouse ovaries and the expression of the core components of the Hippo pathway change during mouse follicular development [42]. In this study, as seen in Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have shown that the Hippo signaling pathway forms a cross network with a variety of factors and multiple signaling pathways such as Notch, TGFβ, c-myc, and PI3K/AKt, which are crucial for the self-renewal and differentiation of stem cells [22,36,37,38,39]. Importantly, several lines of our evidence suggest that the upstream activation of Notch signaling pathways, which have been proven to play a role in germ-line stem cells in ovaries [40,41], and the Hippo signaling pathway have a spatio-temporal correlation with the size of the primordial follicle pool [42]. Hence, the aim of this study is to reflect the variation in the number of OGSCs and explore the expression changes of the core components of the Hippo pathway (MST1, LATS2, YAP1) during physiological aging and pathological aging of OGSCs in the mice OSE layers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the OSE layer has cell-cell contacts and local signaling that may be associated with GSC growth and development [22]. Importantly, evidence suggests that the Hippo signaling pathway is spatiotemporally correlated with the size of the primordial follicle pool [23] and that the existence of OGSCs in the mouse OSE and the expression of OGSCs markers are correlated with both the age of the mouse and with Hippo signaling molecules [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Notably, this provides evidence the Erb-B pathway might be implicated in PCOS, and this pathway is involved in primordial germ cell development in mice [63]. In addition, ERBB3 interacts with YAP1 in the Hippo pathway, which regulates organ size by controlling cell proliferation and apoptosis, and has been associated with primordial follicle pool in mice [64]. Taken together, these five studies provide considerable evidence for the role of the Hippo pathway, neuroendocrine changes (mediated by LHCGR, FSHR and FSHB), and EGFRs in PCOS pathophysiology.…”
Section: Pcosmentioning
confidence: 70%